Pemberdayaan Masyarakat Melalui Pengembangan Usaha Mikro di Kecamatan Tawang Kota Tasikmalaya (Studi pada pelaku usaha mikro yang bergerak pada bidang kuliner) - Mutiara Syipa; Lilis Karwati; Ahmad Hamdan (Yayasan Keluarga Guru Mandiri, 2024)
The ability of micro-business actors to develop their business has not been maximized due to limited knowledge and abilities so that the role of the government is needed to help develop micro-businesses. The research objective is to find out community empowerment through micro business development. The research method used is descriptive qualitative. The techniques used are interviews, observation, and documentation. The targets in this study are micro-business actors engaged in the culinary field. The results showed that community empowerment through micro business development in Tawang District was carried out through the 5P stages, first, enabling starts with building the mindset of micro business actors about the potential that can be developed. Second, strengthening knowledge and skills is done by increasing training that is able to develop the potential of micro business actors including production technique training, processed food training, bakery training, and digital marketing training. Third, protection, namely by assisting the business legality process and halal certification of micro-business actors with easy requirements. Fourth, support, government support for micro business actors includes training support and capital assistance. Fifth, maintenance, routine training activities are carried out at least once a month, and monitoring and evaluation of the program to follow up on the shortcomings of these activities so that they can be improved. Community empowerment activities through micro business development have a significant impact on the increased income of micro business actors and increase the creativity of business actors in innovating products.